Annual report of the Geological Commission. - Corstorphine, G. S. (George Steuart), 1868-1919; Rogers, A. W. (Arthur William), 1872-1946 (s.n.], 1897)
"The reports are issued in two forms; as an ordinary Blue book presented to both houses of Parliament, printed on common paper and in octavo size; and a limited number is printed on thick paper, in small quarto size. The pagination of the First report is different in the two editions, the type having been entirely re-set, but the contents are identical."